Tendencias del crecimiento radial de 23 especies forestales del trópico - LOJAN, L. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The study of monthly growth in circumference of various tropical tree species permitted their grouping by the number of months of this growth. Eight groups of species were found whose growth period varied from five to twelve months during the year. The biggest growth rate was found during the month of July; during the months of February and March the growth rate was lowest, or even non-existent in the majority of species; this finding more or less corresponds with the duration of daylight hours in the locality. The evergreen species were classified in two groups: those of continuous growth and those whose growth was reduced during the months mentioned. The deciduous species were classified in groups of from five to ten months of growth during the year. The species, Juglans boliviana, showed periods of growth and repose that differed from those of the deciduous species native to the northern hemisphere; the most rapid growth was in March. From the group of species studied, it appears the species of rapid growth are those with the longest annual growth period.